Strategi pengembangan layanan perpustakaan dalam menggunakan media sosial di perguruan tinggi - Suherman Suherman (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
This article discusses information technology development strategies for higher education library services. college libraries have specific strategies in developing information technology-based library services more in facing the current industrial revolution 4.0 era in order to improve the quality of services in order to support their educational institutions in realizing "world class university". Therefore libraries based on information technology or better known as digital libraries are very potential to be developed to support a variety of academic activities, especially those relating to the management and utilization of these works. The focus of library digitalization is on four main things, namely procurement, processing, circulation and reference. In this service, digital libraries must be developed optimally in accordance with the advances in information technology today. The use of social media, such as Whatsapp, Line and Twitter, should be considered as an alternative in strategies for developing technology-based library services in universities. Keyword: Information Technology (IT), Library, Digital, whatsapp based service